Evaluation of biomimetic hyaluronic-based hydrogels with enhanced endogenous cell recruitment and cartilage matrix formation. (1st January 2020) - Vainieri, M.L.; Lolli, A.; Kops, N.; D'Atri, D.; Eglin, D.; Yayon, A.; Alini, M.; Grad, S.; Sivasubramaniyan, K.; van Osch, G.J.V.M.
Abstract: Biomaterials play a pivotal role in cell-free cartilage repair approaches, where cells must migrate through the scaffold, fill the defect, and then proliferate and differentiate facilitating tissue remodeling. Here we used multiple assays to test the influence of chemokines and growth factors on cell migration and cartilage repair in two different hyaluronan (HA)-based hydrogels. We first investigated bone marrow Mesenchymal Stromal Cells (BMSC) migration in vitro, in response to different concentrations of platelet-derived growth factor-BB (PDGF-BB), chemokine ligand 5 (CCL5/RANTES) and stromal cell-derived factor 1 (SDF-1), using a 3D spheroid-based assay. PDGF-BB was selected as most favourable chemotactic agent, and MSC migration was assessed in the context of physical impediment to cell recruitment by testing Fibrin-HA and HA-Tyramine hydrogels of different cross-linking densities. Supplementation of PDGF-BB stimulated progressive migration of MSC through the gels over time. We then investigated in situ cell migration into the hydrogels with and without PDGF-BB, using a cartilage-bone explant model implanted subcutaneously in athymic mice. In vivo studies show that when placed into an osteochondral defect, both hydrogels supported endogenous cell infiltration and provided an amenable microenvironment for cartilage production. These processes were best supported in Fibrin-HA hydrogel in the absence of PDGF-BB. This study used an advanced preclinical testing platform to select an appropriate microenvironment provided by implanted hydrogels, demonstrating that HA-based hydrogels can promote the initial and critical step of endogenous cell recruitment and circumvent some of the clinical challenges in cartilage tissue repair. Statement of significance: The challenge of articular cartilage repair arises from its complex structure and architecture, which confers the unique mechanical behavior of the extracellular matrix. The aim of our research is to identify biomaterials for implants that can support migration of endogenous stem and progenitor cell populations from cartilage and bone tissue, in order to permanently replace damaged cartilage with the original hyaline structure. Here, we present an in vitro 3D spheroid-based migration assay and an osteochondral defect model, which provide the opportunity to assess biomaterials and biomolecules, and to get stronger experimental evidence of the not well-characterized dynamic process of endogenous cells colonization in an osteochondral defect. Furthermore, the delicate step of early cell migration into biomaterials towards functional tissue engineering is reproduced. These tests can be used for pre-clinical testing of newly developed material designs in the field of scaffold engineering. Graphical abstract: Image, graphical abstract